MENALI Workshop to Improve Teacher Strategies for Teaching Preschool Children at Risk of Developmental Language Disorder (DLD) - Ayuningtyas, Aradewi Laksmi; Suharso, Puji Lestari; Hapsari, Indri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Developmental language disorder (DLD) is a disorder that affects children's language and/or speech abilities. The diagnosis of DLD usually appears at the age of 5 years and over, but signs of children at risk for DLD begin to appear at the age of 3 years or preschool years. Therefore, the teacher's role is needed in understanding and teaching preschool children at risk of DLD in teaching and learning activities. An intervention program in the form of a MENALI (Mengajar Anak dengan Resiko DLD) workshop was conducted at one of the kindergarten in West Jakarta to improve teacher teaching strategies for preschool children at risk of DLD. The results of the intervention show that this intervention has been shown to significantly improve teacher teaching strategies for preschoolers at risk of DLD. The results of the intervention follow-up also showed that there was progress in the language skills of preschoolers at risk of DLD.Developmental language disorder (DLD) merupakan gangguan perkembangan bahasa yang mempengaruhi kemampuan berbahasa dan/atau berbicara pada anak. Diagnosis DLD biasanya muncul pada usia 5 tahun ke atas, namun tanda-tanda anak dengan resiko DLD mulai terlihat pada usia 3 tahun atau masa usia prasekolah. Oleh karena itu, diperlukan peran guru dalam memahami dan mengajar anak prasekolah dengan resiko DLD dalam kegiatan belajar mengajar. Sebuah program intervensi berupa workshop MENALI (Mengajar Anak dengan Resiko DLD) dilakukan di salah satu KB-TK di Jakarta Barat untuk meningkatkan strategi mengajar guru pada anak prasekolah dengan resiko DLD. Hasil intervensi menunjukkan bahwa program ini terbukti secara signifikan meningkatkan strategi mengajar guru pada anak prasekolah dengan resiko DLD. Hasil follow up intervensi juga turut menunjukkan bahwa terdapat kemajuan kemampuan berbahasa anak prasekolah dengan resiko DLD.